Fish Passage Through Three Types of Structures in Diked Coastal Lake Erie Wetlands. (4th May 2017) - Steinhart, Geoffrey B.; Bode, Sierra; Thieme, Jennifer; Winslow, Christopher J.
Abstract: Over 40% of Great Lakes fishes are wetland dependent, and more than 70% benefit from wetlands periodically. As such, restoration and rehabilitation of Great Lakes coastal wetlands have increased dramatically. This necessitates a balance among varied management objectives, including fish passage. The presence of water control structures commonly found on diked wetlands can limit fish passage if not open all the time. We sampled three diked Lake Erie coastal wetlands to assess how different structures affected fish passage. Water control structures included a pool-and-weir fish ladder, swing gates, and an open culvert. Fyke nets were set five to seven times at each site between April and October 2015. One net was set outside of the wetland, a short distance away from the passage structure, and the other was set inside the wetland, with the net wings enclosing the opening of the structure. Catches were compared for catch rate, three measures of community similarity, and the wetland fish index (WFI). Fish communities on either side of the fish ladder site had low community similarities that were lower than those of the culvert site and similar to those of the swing gate site, suggesting that the fish ladder did not provide fish passage as hoped. Of the three wetlands, catches from inside the wetland with the culvert had a WFI that was most similar to those of wetlands connected to Lake Erie hydrology. Overall, the culvert provided the most opportunity for fish movement into the wetland. However, unlike the other structures, it did not provide a means for precisely managing wetland water levels. Received September 30, 3016; accepted January 25, 2017